Impacts of a decadal drainage disturbance on surface–atmosphere fluxes of carbon dioxide in a permafrost ecosystem - Kittler, Fanny; Burjack, Ina; Corradi, Chiara A.R.; Heimann, Martin; Kolle, Olaf; Merbold, Lutz; Zimov, Nikita; Zimov, Sergey; Göckede, Mathias (Copernicus GmbH, 2016)
Abstract. Hydrologic conditions are a major controlling factor for carbon exchange processes in high-latitude ecosystems. The presence or absence of water-logged conditions can lead to significant shifts in ecosystem structure and carbon cycle processes. In this study, we compared growing season CO2 fluxes of a wet tussock tundra ecosystem from an area affected by decadal drainage to an undisturbed area on the Kolyma floodplain in northeastern Siberia. For this comparison we found the sink strength for CO2 in recent years (2013–2015) to be systematically reduced within the drained area, with a minor increase in photosynthetic uptake due to a higher abundance of shrubs outweighed by a more pronounced increase in respiration due to warmer near-surface soil layers. Still, in comparison to the strong reduction of fluxes immediately following the drainage disturbance in 2005, recent CO2 exchange with the atmosphere over this disturbed part of the tundra indicate a higher carbon turnover, and a seasonal amplitude that is comparable again to that within the control section. This indicates that the local permafrost ecosystem is capable of adapting to significantly different hydrologic conditions without losing its capacity to act as a net sink for CO2 over the growing season. The comparison of undisturbed CO2 flux rates from 2013–2015 to the period of 2002–2004 indicates that CO2 exchange with the atmosphere was intensified, with increased component fluxes (ecosystem respiration and gross primary production) over the past decade. Net changes in CO2 fluxes are dominated by a major increase in photosynthetic uptake, resulting in a stronger CO2 sink in 2013–2015. Application of a MODIS-based classification scheme to separate the growing season into four sub-seasons improved the interpretation of interannual variability by illustrating the systematic shifts in CO2 uptake patterns that have occurred in this ecosystem over the past 10 years and highlighting the important role of the late growing season for net CO2 flux budgets.